Instrumental uncertainty as a determinant of behavior under interval schedules of reinforcement - DeRusso, Alicia; Fan, David; Gupta, Jay; Shelest, Oksana; Costa, Rui M.; Yin, Henry H. (Frontiers in Integrative Neuroscience, 2010)
Interval schedules of reinforcement are known to generate habitual behavior, the performance of which is less sensitive to revaluation of the earned reward and to alterations in the action-outcome contingency. Here we report results from experiments using different types of interval schedules of reinforcement in mice to assess the effect of uncertainty, in the time of reward availability, on habit formation. After limited training, lever pressing under fixed interval (FI, low interval uncertainty) or random interval schedules (RI, higher interval uncertainty) was sensitive to devaluation, but with more extended training, performance of animals trained under RI schedules became more habitual, i.e. no longer sensitive to devaluation, whereas performance of those trained under FI schedules remained goal-directed. When the press-reward contingency was reversed by omitting reward after pressing but presenting reward in the absence of pressing, lever pressing in mice previously trained under FI decreased more rapidly than that of mice trained under RI schedules. Further analysis revealed that action-reward contiguity is dramatically reduced in lever pressing under RI schedules, whereas action-reward correlation does not vary significantly. These data indicate that the extent of goal-directedness could vary as a function of temporal uncertainty.